EFFECT OF GINGER OLEORESIN CONCENTRATION ON THE ENCAPSULATION PROCESS USING IONIC GELATION - Permana, Asep Wawan; Mardiyyah, Annisah; Wiguna, Bangkit; Laksono, Hendrawan; Aji, Galih Kusuma; Mufti, Ayi; Atmaji, Priyo; Muhamaludin; Budiyanto; Kusumasmarawati, Ambar Dwi; Prasetyo, Wegik Dwi; Sulaswatty, Anny; Nasori, Achmad Sofian (Jurnal Teknologi Industri Pertanian, 2024)
The primary active components in ginger oleoresin are gingerol and shogaol, with gingerol exhibiting significant pharmacological activities such as anti-inflammatory, antioxidant, and analgesic effects. However, gingerol is heat-sensitive and degrades at elevated temperatures, limiting its functional efficacy when consumed. To overcome this limitation, encapsulation of ginger oleoresin was performed to enhance its physical and functional properties and improve its bioavailability. This study utilized the ionotropic gelation method to encapsulate ginger oleoresin, resulting in the formation of beads. Alginate was employed as the encapsulation matrix. The dried beads were characterized using FTIR, SEM, disintegration tests, and encapsulation efficiency was assessed via UV-Vis spectrophotometry. Results demonstrated that alginate beads containing ginger oleoresin could be successfully synthesized using the ionotropic gelation technique, with alginate as the polymer and CaCl2 as the cross-linking agent. Ginger oleoresin concentrations of 0.9%, 0.7%, 0.5%, and 0.3% were tested. The highest encapsulation efficiency, 72.48%, was obtained with a ginger oleoresin concentration of 0.7%. Surface morphology analysis revealed that the alginate beads exhibited a rough, porous texture with visible folds. Furthermore, the dry beads disintegrated within 30 minutes. Keywords: alginate, beads, encapsulation, ginger oleoresin, ionic gelation method